Model Pembelajaran Auditory Intelectually Repetition (AIR) Untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa - Siami, Nur; Irawati, Tri Novita (FKIP Universitas Islam Jember, 2021)
This research had a purpose to improve student activity and student learning outcomes by applying the Auditory Intelectually Repetition (AIR) learning model. This study uses Classroom Action Research. The subject of this research were class VIIIA MTs Darul Mukhlashin as recipients of the action and the researcher himself became the giver of it. For collecting datas, this study uses some methods like interviews, observations, tests, and documentation. The result of this research can be seen from the indicators of success. In cycle I, it can be seen that student learning activities gain 76% then in cycle II get 86%. While in cycle I, it can be seen that students learning outcomes was and cycle II was 100%. From these indicators of success, it is concluded that the application of the Auditory Intelectually Repetition learning model to student learning activities and outcomes has increased.